Pemberhentian Tidak Dengan Hormat (PTDH) Anggota Polri Yang Melakukan Tindak Pidana Penyalahgunaan Narkotika Ditinjau Dari Perkap No. 14 Tahun 2011 Tentang Kode Etik Profesi Kepolisian Republik Indonesia - Aji Titin Roswitha Nursanthy; Desy Ratnasari; Tri Romsahadi (LPPM STIH Awang Long, 2022)
Article 30 paragraph (4) of the 1945 Constitution states that the Indonesian National Police as an instrument of the state that maintains security and public order has the duty to protect, protect, serve the community and uphold the law. The formulation of the problem is the mechanism for dishonorably dismissing members of the Police who are involved in the crime of narcotics abuse and the purpose of this study is to find out and analyze the mechanism for the legal process for members of the Police who commit crimes of narcotics abuse in terms of Perkap No. 14 of 2011 concerning the code of ethics for the police profession of the Republic of Indonesia. The type of research carried out includes empirical legal research with a qualitative approach. Based on the results of the research and discussion it can be concluded that members of the Police who commit narcotics crimes must be held accountable for their actions, law enforcement against members of the Police who commit narcotics abuse applies equally to everyone in the eyes of the law.